Calculating the square root with arbitrary order of convergence - Chowdhury, Rezaul Alam; Kaykobad, M. (International journal of computer mathematics, 2000)
In this paper an iterative algorithm has been presented for calculating the square root of a real number with arbitrary order of convergence using formulae derived by applying binomial theorem. The primary objective is to reduce the number of division operations required.